ELEMENTARY ENGLISH TEACHERS' PERCEPTIONS OF MERDEKA CURRICULUM IMPLEMENTATION IN INDONESIAN PRIVATE SCHOOLS: A MIXED-METHODS STUDY - Natasha Elvanuri; Zulfariati; Risza Dwiputri (ELP (Journal of English Language Pedagogy), 2026)
Curriculum reform in Indonesia has led to the implementation of the Merdeka Curriculum, which emphasizes learner autonomy, flexibility, and student-centered learning. Teachers play a central role in translating this reform into classroom practice; however, empirical studies capturing teacher voices in elementary English education remain limited. This study explores English teachers’ perceptions of the Merdeka Curriculum implementation in elementary schools during the 2024/2025 academic year. Using a descriptive quantitative approach, data were collected from eight English teachers in five private elementary schools through a structured questionnaire and supported by semi-structured interviews. Descriptive statistical analysis revealed that teachers expressed predominantly positive perceptions of the curriculum. Specifically, 64% of responses indicated agreement regarding alignment with ministerial regulations, while 63% reflected positive perceptions of English teaching practices under the Merdeka Curriculum. Interview findings further showed that teachers valued the curriculum’s flexibility and its support for active and contextualized English learning, although challenges related to curriculum terminology, instructional preparation, and student engagement were also identified. These findings highlight the importance of incorporating teacher perspectives in curriculum reform and underscore the need for continuous professional development to ensure effective implementation of the Merdeka Curriculum in elementary English learning.